The training of professional engineers fifth International Congress of Engineers, 27 September- 1 October 1971 - Simmons, J. A. 1932- (Institution of Civil Engineers, 1972)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of fifth international congress of engineers; FEANI 20th anniversary held in London on 27 September-1 October 1971.